Ovarian malignant ascites-derived lymphocytes stimulated with prothymosin α or its immunoactive decapeptide lyse autologous tumour cells in vitro and retard tumour growth in SCID mice - Voutsas, I.F.; Pistamaltzian, N.; Tsiatas, M. L.; Skopeliti, M.; Katsila, T.; Mavrothalassiti, I.; Spyrou, S.; Dimopoulos, M.-A.; Tsitsilonis, O.E.; Bamias, A. (European Journal of Cancer, 2013)
Background: Tumour-associated lymphocytes (TALs) present in effusions of ovarian cancer patients exhibit impaired activities, due to the immunosuppressive environment of the ascites. Means to enhance their cytotoxicity against autologous tumour cells are of clinical importance. The immunomodulator prothymosin alpha (proTα) increases the specific lysis of tumour cells by activated CD8+ T-lymphocytes and its immunoreactivity is exerted by the carboxy-terminal decapeptide, proTα(100-109). These two molecules were studied on TALs in vitro, and in SCID mice bearing human ovarian tumours. Methods: TALs and tumour cells were isolated from 41 ovarian cancer patients and co-cultured in the presence of proTα or proTα(100-109). The cytotoxicity of peptide-stimulated TALs was tested against autologous tumour cells and K562. Ex vivo peptide-stimulated TALs from three patients were adoptively transferred intraperitoneally in SCID mice, previously inoculated with each patient's autologous tumour cells. Results: ProTα and its immunoreactive peptide proTα(100-109), enhanced the cytotoxic activity of TALs against autologous tumour cells in vitro, but marginally affected the lysis of K562. The effect of proTα and proTα(100-109) was higher after 7-14 days of stimulation, whereas TAL cytotoxicity was significantly decreased after 21 days. Mice administered TALs, ex vivo activated with proTα or proTα(100-109) for 7 days, showed a relatively lower tumour increase rate and a prolongation of their survial, compared to controls. Conclusion: Our data demonstrate that, in the presence of tumour antigens, proTα and proTα(100-109) enhance the depressed cytotoxicity of TALs against autologous tumour cells in vitro and retard tumour growth in vivo. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Ascites; Human tumour xenografts; Ovarian cancer; Prothymosin alpha; SCID mice; T-cell activation; Tumour-associated lymphocytes